DESIGNING IN-WHEEL SWITCHED RELUCTANCE MOTOR FOR ELECTRIC VEHICLES - Yildirim, M.; Polat, M.; Oksuztepe, E.; Omac, Z.; Yakut, O.; Eren, H.; Kurum, H. (Ieee, 2014)
Estimation of dimension parameters for an electrical machine has great importance before manufacturing. For this reason, analytical design should be performed in an optimum form. While motor analysis is accomplished by package programs, initial size parameters are intutivily provided and then various trials are examined to get optimum results. In this study, we are trying to find dimensional and electrical parameters generating mathematical equations in analytic approaches for In-Wheel Switched Reluctance Motor (IW-SRM), which will be employed by Electric Vehicle (EV). Therefore, optimum motor parameters for required speed and torque have been estimated by solving generated equations for in-wheel SRM with 18/12 poles via MATLAB. Using the parameters, analysis of in-wheel SRM has been carried out 3D Finite Element Method (FEM) by Ansoft Maxwell 15.0 Package Software. Consequently, the accuracy of the estimated parameters has been validated by the results of Maxwell 3D FEM.
16th International Power Electronics and Motion Control Conference and Exposition (PEMC) -- SEP 21-24, 2014 -- Antalya, TURKEY
Keywords: Designing In-wheel SRM; Electric Vehicle; Optimum Parameters Estimation